2016
DOI: 10.1007/s00436-016-5350-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in pancreatic β cell function and Trypanosoma cruzi infection: evidence from human and animal studies

Abstract: The parasite Trypanosoma cruzi causes a persistent infection, Chagas disease, affecting millions of persons in endemic areas of Latin America. As a result of immigration, this disease has now been diagnosed in non-endemic areas worldwide. Although, the heart and gastrointestinal tract are the most studied, the insulin secreting β cell of the endocrine pancreas is also a target of infection. In this review, we summarize available clinical and laboratory evidence to determine whether T. cruzi-infection-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
(97 reference statements)
1
11
0
Order By: Relevance
“…These processes are mediated mainly by bioactive mediators known as adipocytokines, being adiponectin the most studied one in the Chagas Disease. Clinical studies in CCM have shown reduced levels of insulin in these individuals, mainly due to an increase in adiponectin levels, simultaneous to a decrease in leptin levels, among other alterations that promote a change in the function of the stimulus-secretion pathway [32][33][34]. Nevertheless, the study of dos Santos et al reported that among the patients with CD, the individuals with CCM were the only ones with a higher prevalence of T2DM when compared to controls, having the patients with the indeterminate form or the ones with the isolated gastrointestinal form a similar prevalence when compared to healthy volunteers, suggesting that the HF derived from the myocardial involvement of CD may be the primary mechanism of IR in this context [35].…”
Section: Discussionmentioning
confidence: 99%
“…These processes are mediated mainly by bioactive mediators known as adipocytokines, being adiponectin the most studied one in the Chagas Disease. Clinical studies in CCM have shown reduced levels of insulin in these individuals, mainly due to an increase in adiponectin levels, simultaneous to a decrease in leptin levels, among other alterations that promote a change in the function of the stimulus-secretion pathway [32][33][34]. Nevertheless, the study of dos Santos et al reported that among the patients with CD, the individuals with CCM were the only ones with a higher prevalence of T2DM when compared to controls, having the patients with the indeterminate form or the ones with the isolated gastrointestinal form a similar prevalence when compared to healthy volunteers, suggesting that the HF derived from the myocardial involvement of CD may be the primary mechanism of IR in this context [35].…”
Section: Discussionmentioning
confidence: 99%
“…the pancreas. Previous work on intracellular parasites including T. cruzi (Corbett et al, 2002;Dufurrena et al, 2017;Martello et al, 2013), Plasmodium (Abhilash et al, 2016;Glaharn et al, 2018) and Toxoplasma (Nassief Beshay et al, 2018), has reported sequestration in pancreatic blood vessels, pancreatic invasion, and morphological changes in the pancreas, including acute pancreatitis in humans. The fact that the pancreas represents one of the largest reservoirs of an extracellular parasite such as T. brucei is puzzling, as the majority of the organ consists of exocrine tissue which produces pancreatic enzymes for digestion including trypsin and chymotrypsin to digest proteins, amylase to digest carbohydrates, and lipase to break down fats (Shi and Liu, 2014).…”
Section: Parasite Reservoirs and Pathologymentioning
confidence: 97%
“…Acute and subacute T . cruzi infection produce a complex pattern of changes in host insulin secretion characterized by hypoinsulinemia with accompanying hyperglycemia [ 13 ]. During acute infection, T .…”
Section: T Cruzimentioning
confidence: 99%
“…Additionally, other contributors to hypoinsulinemia during infection include pathogen-induced autonomic disruption of the parasympathetic innervation of the pancreas through denervation [ 15 , 16 ]. Because pancreatic secretion of insulin relies on parasympathetic neuronal inputs [ 17 ], parasympathetic denervation may contribute to the diminished insulin secretion in Chagas disease [ 13 ]. Infection also elevates glucagon levels, which further disrupts glucose homeostasis and leads to host hyperglycemia [ 13 ].…”
Section: T Cruzimentioning
confidence: 99%
See 1 more Smart Citation